Rediscovering wisdom through animated da’wah series for children - Mohd Daud, Nurfarhana; Md Ajis, Ahmad Fuzi; Aziz, Siti Noor Ain; Mohammed Zabidi, Mahfuzah; Abu Bakar, Muhamad Afiq Hazwan; Omar, Naqib Zharfan Basysyasy (Universiti Teknologi MARA, Kedah, 2022)
The challenge of western thought that is not dealt with properly can weaken Muslims’ hold on the teachings of the Prophet SAW. Scholars' guidelines sourced from Al-Quran and As-Sunnah need to be highlighted in a more easily accepted and understood form by the general public. Imam Badiuzzaman Said Nursi's work Risalah An-Nur, a Tafsir book, is referred to in this project. The wisdom and advice in his works are transformed into comics and animations that all groups, especially children, can easily understand. This animation aims to spread the knowledge and wisdom of Said Nursi's thoughts to a broader audience. Animation production involves four levels, namely (1) storyboard illustration; (2) model and character developers; (3) animation; and (4) video editing. It is hoped that it can bring Muslims closer to the works of scholars of the past, which contain guidelines and wisdom that are relevant and thorough in solving the problems of the present and the future, even though they have been separated for decades.